2020
DOI: 10.1093/jisesa/ieaa100
|View full text |Cite
|
Sign up to set email alerts
|

Tenebrio molitor (Coleoptera: Tenebrionidae)—Optimization of Rearing Conditions to Obtain Desired Nutritional Values

Abstract: The present study dealt with the influence of temperature and feed on the nutritional value of Tenebrio molitor, especially on the content of crude protein, amino acids, fat, and fatty acid profile. Tenebrio molitor larvae were kept in 15, 20, and 25°C and fed with wheat bran, lentil flour, and mixture. The parameters were analyzed by international standard methods. Generally, with an increase of the lentils in the feed, the crude protein content increased. The changes in the temperature and the feed were most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 27 publications
2
26
1
Order By: Relevance
“…The fatty acids profile in control larvae (Table 4) shows that the prevalent fatty acids were among saturated (SFA) palmitic, myristic and stearic, among monounsaturated (MUFA) oleic (C18:1) and palmitoleic (C16:1), and among polyunsaturated fatty acids (PUFA) linoleic acid. These results are in good agreement with previous reports (Table 2S) [11,37], although that fatty acid content has been reported to greatly depend on feed and rearing temperature [73]. Oleic (C18:1) and linoleic acid (C18:2) formed the two major fatty components of TML in all series.…”
Section: Fatty Acid Analysessupporting
confidence: 93%
“…The fatty acids profile in control larvae (Table 4) shows that the prevalent fatty acids were among saturated (SFA) palmitic, myristic and stearic, among monounsaturated (MUFA) oleic (C18:1) and palmitoleic (C16:1), and among polyunsaturated fatty acids (PUFA) linoleic acid. These results are in good agreement with previous reports (Table 2S) [11,37], although that fatty acid content has been reported to greatly depend on feed and rearing temperature [73]. Oleic (C18:1) and linoleic acid (C18:2) formed the two major fatty components of TML in all series.…”
Section: Fatty Acid Analysessupporting
confidence: 93%
“…These fat content values were higher than reported by Bednářová et al [39] (36.1%) or Finke [40] (35.0%). In contrast, the content of 6.4% [43], 8.9% [44] or 14.6% [8] were reported as one of the lowest values of fat content. In accordance with the period of starvation, the fat content may further decrease [8].…”
Section: Influence Of Feed On Crude Protein and Fat Contentmentioning
confidence: 82%
“…In contrast, the content of 6.4% [43], 8.9% [44] or 14.6% [8] were reported as one of the lowest values of fat content. In accordance with the period of starvation, the fat content may further decrease [8]. Depending on the feed, Broekhoven et al [11] reported a range from 18.9 to 27.6%.…”
Section: Influence Of Feed On Crude Protein and Fat Contentmentioning
confidence: 82%
See 1 more Smart Citation
“…Working with the same insect species, Yang and Tomberlin (2020) compared the life-history traits of H. illucens larvae at bench-top and industrial scale regarding survival, biomass production and waste conversion, and highlight the significance of scale effect when evaluating the industrial value of research results. The ability to manipulate insect nutritional values by altering rearing conditions was studied by Adámková et al (2020) , who demonstrated the effect of temperature and diet on the nutrient composition of T. molitor larvae. Similarly, Silva et al (2021) evaluated the development and nutrient composition of T. molitor larvae fed poultry litter-based diets.…”
Section: Contributions To This Special Issuementioning
confidence: 99%